THE INFLUENCE OF PHYSICAL WORK ENVIRONMENT, NON-PHYSICAL WORK ENVIRONMENT, WORKLOAD AND TRANSFORMATIONAL LEADERSHIP STYLE ON CV EMPLOYEE PERFORMANCE. PUTRA PERKASA JAYA - Gautama, Gilang; Winahyu, Pawestri; Reskiputri, Tatit Diansari (Dynamic Management Journal, 2025)
Company really needs efforts that can improve employee performance to achieve or even exceed the targets set by the company. This study aims to determine and analyze the influence of the physical work environment, non-physical work environment, workload and transformational leadership style on employee performance at CV. Putra Perkasa Jaya, Banyuwangi Regency. This type of research uses a quantitative method with a sample size of 54 respondents and uses a Nonprobability sampling technique with a saturated sampling technique using a data collection technique in the form of a questionnaire to respondents. The data analysis technique for this study uses instrument testing, classical assumptions, multiple linear regression, hypotheses and coefficients of determination. The results of the analysis obtained indicate that the physical work environment, non-physical work environment, workload and transformational leadership style have a positive and significant effect partially on employee performance at CV. Putra Perkasa Jaya, the results of the R2 Determination Coefficient test with a contribution level of influence of 0.927 or 93%.